Micro‐Supercapacitors: Aqueous MXene/PH1000 Hybrid Inks for Inkjet‐Printing Micro‐Supercapacitors with Unprecedented Volumetric Capacitance and Modular Self‐Powered Microelectronics (Adv. Energy Mater. 23/2021). Issue 23 (17th June 2021) - Ma, Jiaxin; Zheng, Shuanghao; Cao, Yuexian; Zhu, Yuanyuan; Das, Pratteek; Wang, Hui; Liu, Yu; Wang, Jiemin; Chi, Liping; Liu, Shengzhong (Frank); Wu, Zhong‐Shuai
Abstract : In article number 2100746, Shengzhong (Frank) Liu, Zhong‐Shuai Wu and co‐workers report an aqueous MXene/PH1000 hybrid ink for inkjet printing of planar micro‐supercapacitors, which can serve as a flexible energy storage unit for Si film solar cells and can supply power for printable temperature sensors. Such printable inks are expected to allow for scalable and customizable fabrication of power sources for next‐generation, self‐sustaining, wearable, and implantable microelectronics.